Preliminary Assessment of Chinese Strategy in Controlling Reemergent Local Outbreak of COVID-19 - Wang, Zhouhan; Jin, Yanqi; Jin, Xi; Lu, Yingfeng; Yu, Xiaopeng; Li, Lanjuan; Zhang, Yimin (Frontiers in Public Health, 2021)
Reemergent local outbreaks of coronavirus disease 2019 (COVID-19) have occurred in China, yet few about Chinese response strategy and its evaluation have been reported. This article presents preliminary assessment of Chinese strategy in controlling reemergent local outbreaks of COVID-19. Time course of accumulative and daily new cases as well as time-varying reproductive numbers (Rt) of outbreak areas were presented. The asymptomatic rate, days required to control the outbreaks, seeding time (ST) and doubling time (DT) of areas with over 96 reemergent cases were calculated. National and local year-on-year growth rate of gross domestic product (GDP) were presented. Accumulative 30, 8, 11, 430, 15, 139, 1067, 382, 42 and 94 confirmed reemergent COVID-19 cases were diagnosed in Hulun Buir, Shanghai, Tianjin, Kashgar, Qingdao, Dalian, Urumchi, Beijing, Jilin and Harbin respectively. Among them, maximum asymptomatic infections rate was 81.9%. Time required to control local outbreak in the areas above varied from 29 to 51 days. After activation of outbreak responses, the late-stage DTs of Kashgar, Urumchi, Beijing and Dalian were apparently lengthened compared to the early-stage DTs. Although year-on-year GDP growth rate of Urumchi was slightly affected, GDP growth of Dalian, Beijing, Jilin, Harbin kept rising during the reemergence. Moreover, year-on-year GDP growth rate of mainland China turned positive regardless of the reemergent local outbreaks. In general, Chinese strategy to maintain the status of no or minimal transmission was effective in balancing COVID-19 reemergent local outbreak control and economic recovery.